A Comparative study of some Immunological and Molecular Techniques to Detect Cytomegalovirus in patients with Kidney Failure in Diyala Governort - Shahad Shaker Mahmood; Abbas Abod Farhan; Mohmmed Abdul Daim Saleh (Diyala Journal of Medicine, 2018)
Background: Kidney failure can be defined as the total failure of toxins and waste from filtration the blood. This disease is characterized by reduced glomerular filtration rate (GFR) to about 20-50% , resulting in the failure to regulate the amount of fluid in the body and it is divided into two types  acute and chronic renal failure .The immunity of patients with haemodialysis becomes weak and this cause viral infections such as     Cytomegalovirus human cells.